The Influence of Work-Life Balance on Job Satisfaction with Burnout as an Intervening Variable - Savigo, Al Fath Demas; Nurhasanah, Siti; Febriani, Rizki (Jurnal Manajemen Bisnis dan Kewirausahaan, 2023)
The aim of this research is to determine the influence of work-life balance on job satisfaction mediated by burnout. This research was conducted at PT Pesona Indonesia Plywood Industri (PIPI), involving 82 employees in the veneer division. This research uses quantitative methods with a descriptive approach and analyzes with path analysis. From result of this research was work-life balance has a positive and significant effect on job satisfaction. Work-life balance has a negative and significant effect on burnout, and burnout has a negative and significant effect on job satisfaction. Moreover, work-life balance has a positive and significant effect on job satisfaction through burnout.